PENGEMBANGAN SISTEM PENJAMINAN MUTU LAYANAN PENDIDIKAN DASAR–MENENGAH MELALUI AUDIT INTERNAL DAN PELATIHAN KARYAWAN - Uning Heri Gagarin; Yeni Trisna Purba; Frans Favo Purba S (Yayasan Nusantara Hasana Berdikari, 2025)
This community service activity (PkM) aims to develop and strengthen the Quality Assurance System for primary and secondary education services through the implementation of internal audits and staff training (teachers and education personnel). The partners’ challenges generally include poorly organized quality documents, non-standardized service SOPs, program implementation that is not consistently aligned with plans, a lack of routine data-based monitoring, and undocumented follow-up actions on findings. The interventions are carried out through mapping educational service processes, developing standards/SOPs and audit instruments, training internal auditors and service staff (academic administration, student services, and parent services), conducting internal audits in priority areas, and assisting in the preparation of corrective and preventive action (CAPA) plans. The main outputs include a concise quality manual, a package of SOPs, audit instruments, audit reports and follow-up action plans, as well as a PDCA (Plan–Do–Check–Act) cycle mechanism ready for sustainable implementation.